2022
DOI: 10.1017/jfm.2022.591
|View full text |Cite
|
Sign up to set email alerts
|

Chordwise flexible aft-tail suppresses jet-switching by reinstating wake periodicity in a flapping foil

Abstract: The effect of a chordwise flexible aft-tail of a rigid heaving aerofoil on the dynamical transitions of the trailing-wake is studied here. The two-way coupled fluid–solid dynamics is simulated using an in-house fluid–structure interaction (FSI) platform, comprising a discrete forcing immersed boundary method based incompressible Navier–Stokes solver, weakly coupled with a finite difference method based structural solver. The FSI dynamics is studied in comparison to the corresponding rigid tail configuration. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…In the context of thrust generation, Bøckmann and Steen ( 14 ) reported the adjustment of phase-offset values to optimal ranges of load production in a flapping airfoil, with the help of passive oscillations. Marais et al ( 15 ), Shinde and Arakeri ( 16 ), and Shah et al ( 17 ) demonstrated the capability of passive pitching of chordwise flexible foils in inhibiting symmetry breaking and jet-switching phenomena of the trailing-wake. These studies underline the importance of passive oscillations in controlling the flow-field as well as the loads.…”
Section: Introductionmentioning
confidence: 99%
“…In the context of thrust generation, Bøckmann and Steen ( 14 ) reported the adjustment of phase-offset values to optimal ranges of load production in a flapping airfoil, with the help of passive oscillations. Marais et al ( 15 ), Shinde and Arakeri ( 16 ), and Shah et al ( 17 ) demonstrated the capability of passive pitching of chordwise flexible foils in inhibiting symmetry breaking and jet-switching phenomena of the trailing-wake. These studies underline the importance of passive oscillations in controlling the flow-field as well as the loads.…”
Section: Introductionmentioning
confidence: 99%